PENGUJIAN AKTIVITAS ANTIMIKROBA EKSTRAK ETIL ASETAT DAN METANOL KAYU RANTING SENGON (Falcataria moluccana) SAKIT - Popy Listiani; Popy Hasanah; Alfi Rumidatul; Feldha Fadhila; Yayan Maryana (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Klebsiella pneumoniae, Shigella dysenteriae, Salmonella typhi, Escherichia coli, and Candida albicans are the microorganisms that most often infect. Infectious diseases can be cured and the transmission is minimized using various kinds of antibiotics.The search for antimicrobial compounds from nature is expected to reduce the negative effect of antibiotics. One of the plants suspected of having antimicrobial content is the sengon tree. This study aims to determine the ability of sengon sore wood extract with ethyl acetate and methanol as an antimicrobial solvent. The test method used is Kirby bauer with treatments 9%, 9.5%, 10%, 10.5%, and 11%. The result of this study showed that the ethyl acetate extract of sengon sick wood showed antimicrobial activity against Shigella dysenteriae at all concentrations and in Klebsiella pneumoniae only at a concentration of 11%, there’s no antimicrobial activity against E. coli. A Methanol extract of sengon sick twig wood showed antimicrobial activity against Klebsiella pneumoniae at concentrations of 10%, 10.5%, 11%, and on Candida albicans at all concentrations, but didn’t show antimicrobial activity against E. coli, S. typhi, and S. dysenteriae. Can be concluded that the ethyl acetate extract of sengon sick wood branches could inhibit the growth of Shigella dysenteriae and Klebsiella pneumoniae. Meanwhile, methanol extract of sengon sick twig wood can inhibit the growth of Klebsiella pneumoniae and Candida albicans.